KONSEP MANUSIA MUSLIM BERKEMAJUAN DALAM PERSPEKTIF AL-QUR’AN SURAT AL-MUJADALAH AYAT 11 - Ummah Karimah (Universitas PTIQ Jakarta, 2024)
Human existence both as social and individual beings will certainly require knowledge in carrying out their role in life in the world. This study aims to determine the concept of Muslim human progress in the perspective of al-Qur'an Surat Al-Mujadalah verse 11. The research method used is library research with descriptive qualitative research. The results obtained from data analysis are that the concept of progressive Muslim man in the perspective of al-Qur'an Surat Al-Mujadalah verse 11 is (1) Muslim man who has strong faith and aqidah, especially in running his life in the world. (2) Muslims who make the Qur'an as a guide and differentiator between right and wrong in their lives and with knowledge Allah raises their degrees higher than other Muslims. (3) servants of the most merciful Allah.